THE EFFECT OF ENTREPRENEURSHIP EDUCATION, INNOVATION, AND ENTREPRENEURIAL MOTIVATION ON ENTREPRENEURIAL INTEREST IN STUDENTS OF THE FACULTY OF ECONOMICS, STATE UNIVERSITY OF JAKARTA - Chairunnisa; Purwana, Dedi; Munawaroh (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2022)
This study aims to determine the effect of entrepreneurship education, innovation, and entrepreneurship motivation on the interest in entrepreneurship of students of the Faculty of Economics, State University of Jakarta batch 2017. This research was conducted for 9 months starting from January 2021 to September 2021. The method used in this study is the method survey. Technique uses Proportional Stratified Random Sampling with a sample of 149 respondents from students of the Faculty of Economics UNJ majoring in Economics and Administration class 2017. The data was collected through distributing questionnaires using a Likert scale. Based on the results of the research conducted, it was found that Entrepreneurship Education has a positive and significant effect on Interest in Entrepreneurship. Innovation has a positive and significant effect on Interest in Entrepreneurship. Entrepreneurial Motivation has a positive and significant effect on Interest in Entrepreneurship. According to the research hypothesis.